IXPE observation confirms a high spin in the accreting black hole 4U 1957+115 - Marra, L. (EDP Sciences, 2025)
We present the results of the first X-ray polarimetric observation of the low-mass X-ray binary 4U 1957+115, performed with the Imaging X-ray Polarimetry Explorer in May 2023. The binary system has been in a high-soft spectral state since its discovery and is thought to host a black hole. The ∼571 ks observation reveals a linear polarisation degree of 1.9% ± 0.6% and a polarisation angle of −41◦. 8 ± 7◦. 9 in the 2–8 keV energy range. Spectral modelling is consistent with the dominant contribution coming from the standard accretion disc, while polarimetric data suggest a significant role of returning radiation: photons that are bent by strong gravity effects and forced to return to the disc surface, where they can be reflected before eventually reaching the observer. In this setting, we find that models with a black hole spin lower than 0.96 and an inclination lower than 50◦ are disfavoured.